Greek-language education abroad and ‘New’ Migration: the case of the Greek schools in Germany - Aspasia Chatzidaki (Cahiers Balkaniques)
This paper reports on a qualitative study investigating a particular type of Greek-language education abroad (‘non-mixed’ Greek schools in Germany) and how their teachers view the functions such educational settings serve in the era of ‘new’ migration from Greece. These schools (K-12) follow the Greek curricula and employ teachers seconded from Greece. Following the decision of Greek authorities to start abolishing them in 2011, Greek non-mixed schools saw their students’ numbers wane. ‘New’ migration, however, has led to an important increase in enrolments and a change in the student population’s profile. Οur findings suggest that teachers consider them as irreplaceable, not only because they help maintain a sense of Greek identity among immigrant youths but also because they are believed to be the only educational institution which covers the needs of ‘new’ immigrant students facing important educational and psychological challenges.